Cold pursuit - Parker, T. Jefferson (New York : Hyperion, 2003)
Homicide cop Tom McMichael must put aside generations of bad blood between the McMichael and the Braga families when he is assigned to investigate the murder of eighty-four-year-old city patriarch Pete Braga who was found bludgeoned to death.
National College of Business and Arts
Keywords: Police -- Fiction; Detective and mystery fiction